Emergence of Internet Usage: Impact Analysis on the Performance of Small and Medium-sized Enterprises, a Case Study of Manufacturing Companies in Analamanga Region- Antananarivo Madagascar - Ratojoarivelo Setriniaina Henri; Etienne Stefano Raherimalala; Ranjatson Jean Patrick; Andrianjary Myriam; Fidelio Arnold Ulrich; Ratiarimananjatovo Narindra; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
The advent of digitization has unlocked numerous avenues for a country's economic advancement, particularly benefiting small and medium-sized enterprises (SMEs). With the ubiquitous presence of Internet technologies, the landscape has undergone a rapid transformation. Today's business environment differs significantly from both the past and the anticipated future. The integration of the Internet into business operations has spurred significant innovations across various sectors. Nevertheless, leveraging the Internet in business operations offers flexibility and substantial leeway in terms of organizational structure and management practices. However, limited financial resources pose a significant barrier to widespread Internet adoption in businesses. Additionally, coping with technological advancements remains a pressing challenge for businesses' economic development. Our research hypothesis posits that a coherent and strategic utilization of the Internet yields notable impacts on business performance. Our research aims to delineate the various ways in which businesses employ the Internet and to underscore its influence on business performance. We conducted surveys on more than 125 small and medium-sized manufacturing enterprises in downtown Antananarivo-Madagascar and its environs between 2021 and 2023. The gathered data underwent statistical analysis using SPSS and XLSTAT software.